HUBUNGAN PEMBELAJARAN DARING TERHADAP KECEMASAN PADA MAHASISWA TINGKAT AKHIR DI MASA PANDEMI COVID-19 - Jessisca, Inggit; Sriningsih, Nining (Nusantara Hasana Journal, 2021)
Online lectures or commonly referred to as online are a form of using the internet that can increase the role of students in the learning process. The term online is an acronym for "In the Network" so online lectures are one of the online learning methods or are carried out through the internet network. Some of the requirements for implementing online lectures include: the organizers of online lectures, positive mindsets for lecturers and students in the main function of the internet, the design of a learning process system that can be learned by all students and a feedback mechanism from the organizers. Stress that arises during the COVID-19 pandemic can be in the form of fear and anxiety about personal health. Adolescents feel burdened with academic pressure, are anxious about not being able to follow online learning well, the workload is felt to be piling up, unable to do assignments and the network is not supportive during online learning (WHO, 2019) Objective: This study was conducted to determine the relationship between online learning and student anxiety during the covid pandemic at STIKes Yatsi Tangerang Research design: The research design used by the current researcher is a quantitative study with a descriptive correlation research design, which is a study used to express a relationship between variables that have two or more variables. The relationship between online learning and anxiety in final year students during the Covid-19 pandemic Result: The univariate analysis in this study aims to see the proportion and frequency distribution of student characteristics, namely age and gender. Respondents in this study were final year students at STIKes Yatsi Tangerang. it is known that from 109 students aged <22 years 83 respondents (76.1%) while age>22 years 26 respondents (23.9%) and male 38 respondents (34.9%) female 71 respondents (65 ,1%) Conclusion: Based on the age characteristics of the respondents in table 5.1.1 that the age of the dominant respondents in this study is age <22 years as many as 83 respondents (76.1%) of 109 respondents Suggestion: hopefully lecturers can have a good video or the way it is delivered is as attractive as possible during online learning in order to reduce anxiety in students so that they can take part in learning lessons as expected in the learning objectives